Journalism pedagogy and ICTs in a time of pandemic: A case study of selected journalism schools in Southern Africa - Msimanga, Mbongeni; Tshuma, Lungile; Matsilele, Trust (World of media, 2022)
The paper explores journalism pedagogy in selected Southern African journalism schools. It draws from two South African Universities: The Cape Peninsula University of Technology (CPUT) Journalism Department and the School of Communication at the University of Johannesburg (UJ). From Zimbabwe, it draws on Journalism and Media Departments: The National University of Science and Technology (NUST) and Media and Society Studies at Midlands State University (MSU). The paper utilises the Domestication theory and Replacement model as theoretical paradigms to assess how the selected journalism schools reconfigured teaching and learning on their practical and theoretical subjects during the COVID-19 pandemic era. Semi-structured interviews are used with students and journalism educators to understand strategies adopted in the deployment of lectures. The study aims at understanding the teaching techniques that were adopted by journalism educators during the pandemic and how students adopted to virtual delivered education. Lastly, we solicit views from students who were already seeking or had been placed on attachment or work-related learning to establish how they readjusted, if at all. The study found that teaching practical courses was a challenge because, for example, editing suits for film and radio courses are housed on campus. For Zimbabwean universities, the challenge was that students were not given data by the University for online learning while lecturers’ data was not enough for their teaching. This is in contrary to South Africa were both lecturers and students were given data, laptops and other gadgets for online learning. Despite challenges faced during the COVID-19 pandemic, lecturers received training on how to conduct online lessons and restructured their syllabus to ensure that it meets the demands of the ‘new normal’.